MEASURING MARKET RISK USING STATISTICAL METHODS - URBANIKOVA, Marta (Trends in education, 2011)
The aim of this article is to charakterize kanking risks and methods of their measuring in accordance with international standards of Basel II. Compares the methods for calculating the market risk of the banking portfolio, such as variance - covariance method, a method of historical earnings, Monte Carlo simulation methods, Delta - Gamma (Theta) method, Method Expected shortfall and others.
Keywords: risk management; market risk; Basel II; Value at Risk; portfolio.